A palladium-catalyzed regiocontrollable hydroarylation reaction of allenamides with B2pin2/H2O. Issue 30 (26th March 2019) - Cui, Jie; Meng, Long; Chi, Xiaochen; Liu, Qing; Zhao, Pingping; Zhang, Dao-peng; Chen, Lei; Li, Xinjin; Dong, Yunhui; Liu, Hui
Abstract : A novel palladium-catalyzed regiocontrollable hydroarylation reaction of allenamides with B2 pin2 /H2 O has been disclosed. Abstract : A novel palladium-catalyzed regiocontrollable hydroarylation reaction of allenamides with B2 pin2 /H2 O has been disclosed. H2 O as an ideal hydrogen source was activated by B2 pin2 to furnish allylamines or enamines with a broad functional group tolerance. The regioselectivity for both of the two products was up to 99 : 1 for most of the examples, which was achieved by adjusting the addition order of the catalyst and iodobenzene derivatives. The tentative investigation of the mechanism proved the reaction to be a non-radical process and the deuterium-labeled experiments indicated that the hydrogen was from H2 O.